Kajian Potensi Erosi Di Daerah Aliran Sungai Babon Menggunakan Permodelan GeoWEPP - Revangga Dandha Pratama; Dimas Jalu Setyawan; Budi Santosa (Universitas Katolik Soegijapranata Semarang, 2019)
At the time of the high intensity of rainfall in Semarang, the water contained in the Babon River had overflowed, resulting in flooding of parts of the area adjacent to the Babon river flow. This matter has many factors, there are erosion and sediment produced. This study aims to study erosion potential in the Babon watershed, using the Geospatial Interface for Water Erosion Prediction Project (GeoWEPP) modeling. The results of the modeling are the amount of erosion rate and erosion distribution in the study area. The erosion prediction period in this study is in 2006 - 2015. Data needed in GeoWEPP operation are Digital Elevation Model, climate data, land use data, and soil type data. Based on the GeoWEPP process in the Babon watershed the erosion rate was 36.1 tons / ha / year and the sediment yield was 26075.2 tons / year. From the results of the erosion rate produced divided by the reasonable erosion rate get the Erosion Hazard Level index (TBE) of 3.6 or including medium TBE. Based on the distribution of erosion maps produced, the area experienced the greatest erosion rate in the Ungaran region. This is due to the fact that it belongs to the highlands and has a high slope value.